Isoproterenol-Dependent Activation of TRPM7 Protects Against Neurotoxin-Induced Loss of Neuroblastoma Cells - Sun, Yuyang; Kamat, Amrita; Singh, Brij B. (Frontiers in Physiology, 2020)
Activation of ion channels is essential for neuronal physiology and its survival. Loss of ion channel function is known to be associated with several neurodegenerative diseases such as Parkinson’s that exhibit loss of dopaminergic neurons; however, mechanisms that could limit neuronal loss are not yet fully identified. Our data suggest that neurotoxin-mediated loss of neuroblastoma SH-Sy5Y cells is inhibited by the addition of -adrenergic receptor (β-AR) agonist isoproterenol. The addition of isoproterenol to SHSY-5Y cells showed increased Mg2+ influx and a dose-dependent increase in cell survival was observed in the presence of neurotoxin and isoproterenol. Importantly, isoproterenol potentiated the activation of the transient receptor potential melastatin-7 (TRPM7) channel that increases intracellular Mg2+ levels. The addition of 2APB, which is a known TRPM7 channel blocker, significantly decreased the TRPM7 function and inhibited isoproterenol-mediated protection against neurotoxins. Moreover, neurotoxins inhibited TRPM7 expression and function, but the restoration of TRPM7 expression increased neuroblastoma cell survival. In contrast, TRPM7 silencing increased neuronal loss, decreased Mg2+ homeostasis, and inhibited mitochondrial function. Moreover, isoproterenol treatment prevented neurotoxin-mediated loss of TRPM7 expression and inhibited Bax expression that induces cell survival. These effects were dependent on the neurotoxin-induced increase in oxidative stress, which inhibits TRPM7 expression and function. Overall these results suggest a significant role for β-AR in activating TRPM7 channels that regulate Mg2+ homeostasis and are essential for the survival of neurotoxin-induced loss of SH-SY5Y cells.